2021
DOI: 10.3390/ani11020468
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Whole Sesame Seeds on the Expression of Key-Genes Involved in the Innate Immunity of Dairy Goats

Abstract: Whole sesame seeds (WSS) are rich in both linoleic acid (LA) and lignans. However, their impact on the innate immunity of goats is not well studied. Twenty-four goats were divided into three homogeneous sub-groups; comprise one control (CON) and two treated (WWS5 and WWS10). In the treated groups, WSS were incorporated in the concentrates of the CON at 5 (WSS5) and 10% (WSS10) respectively, by partial substitution of both soybean meal and corn grain. The expression levels of MAPK1, IL6, TRIF, IFNG, TRAF3, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 83 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…Many studies on diet use whole grains, seeds, or fruits as a food source of lignans . Research has revealed that in almost all subjects, dietary intervention with lignan-rich foods (mostly flaxseed and sesame) can increase the level of ENL in the blood. , Food is a complex system, and lignans in food may act synergistically with other components. Studies have demonstrated that the consumption of flaxseed, which contains both lignans and omega-3 fatty acids, can work together to effectively prevent colon cancer .…”
Section: Digestion Absorption and Transformation Of Lignan In Vivo An...mentioning
confidence: 99%
“…Many studies on diet use whole grains, seeds, or fruits as a food source of lignans . Research has revealed that in almost all subjects, dietary intervention with lignan-rich foods (mostly flaxseed and sesame) can increase the level of ENL in the blood. , Food is a complex system, and lignans in food may act synergistically with other components. Studies have demonstrated that the consumption of flaxseed, which contains both lignans and omega-3 fatty acids, can work together to effectively prevent colon cancer .…”
Section: Digestion Absorption and Transformation Of Lignan In Vivo An...mentioning
confidence: 99%